How safe is my food? Assessing the effect of information and credible certification on consumer demand for food safety in developing countries - Birol, Ekin; Roy, Devesh; Torero, Máximo (International Food Policy Research Institute, 2010)
The literature regarding consumer demand for safer food in developing countries is scant, and the general assumption is that these consumers' willingness to pay (WTP, as an indicator of their demand) is constrained by their low ability to pay (ATP). There are, however, a number of developing countries with growing middle-income populations whose ATP has been steadily increasing, although low food safety standards in these countries still prevail. In this paper, we argue that ATP, while necessary, is not the sole condition for WTP and that credible information about and certification of food safety are required to ensure that ATP translates into WTP. To test this hypothesis, we conducted a randomized market experiment in two branches of a supermarket chain in Mumbai, India, a city that hosts one of the world's fastest growing middle-income populations. In this experiment, we sold grapes with credible food safety certification labels and the exact same grapes (a placebo) without such labels. We provided all consumers with extensive food safety information comprising banners and posters announcing the sale of food-safety-certified grapes in the supermarket. We also randomly selected one-half of the consumers and provided them with intensive information (a short documentation flier) describing what credible certification of food safety entails. By continuously varying the prices (with the labeled grapes priced higher than unlabeled ones) during the month in which the experiment was implemented, we found that those consumers who received intensive information (the treatment group) are more likely to purchase grapes labeled as certified. This result is robust to the inclusion of an extensive set of controls (income, gender, and education) gathered through a structured survey instrument implemented following the purchase of the grapes. To further investigate the marginal impact of credible information on consumer demand for food safety, we studied consumers' answers to various knowledge, attitude, perception, and practice (KAPP) questions also collected through the survey instrument. Using KAPP responses, we created a consumer-specific food safety consciousness index (FSCI) and stratified consumers according to those below and those above the sample mean FSCI. We find that the marginal impact of credible information and certification on the purchase of labeled grapes is significantly greater for consumers with higher FSCI. We therefore conclude that credible information and certification are important determinants of consumer demand for food safety.